Interactive Effects of CO2 Concentration and Water Regime on Stable Isotope Signatures, Nitrogen Assimilation and Growth in Sweet Pepper - Serret, María D.; Yousfi, Salima; Vicente, Rubén; Piñero, María C.; Otálora-Alcón, Ginés; del Amor, Francisco M.; Araus, José L. (Frontiers in Plant Science, 2018)
Sweet pepper is among the most widely cultivated horticultural crops in the Mediterranean, being frequently grown hydroponically under cover in combination with CO2 fertilization and water conditions ranging from optimal to suboptimal. The aim of this study is to develop a simple model, based on the analysis of plant stable isotopes in their natural abundance, gas exchange traits and N concentration, to assess sweet pepper growth. Water regime affects plant growth via nitrogen assimilation, which is associated with the transpiration stream, particularly at high [CO2], while the lower N concentration caused by rising [CO2] is not associated with stomatal closure. The stable isotope composition of carbon, oxygen and nitrogen (δ13C, δ18O and δ15N) in plant matter are affected not only by water regime but also by [CO2]. The way that δ13C explains differences in plant growth across water regimes seems to be mediated through its direct relationship with N accumulation in leaves. The changes in the profile and amount amino acids caused by water stress and high [CO2] support this conclusion. However, the results do not support the use of δ18O as an indicator of the effect of water regime on plant growth.